Pengaruh Dukungan Supervisor dan Pemberdayaan Terhadap Organizational Citizenship Behavior - Nursanti, Tinjung Desy; Anissa, Aida Dwi (Bina Nusantara University, 2014)
Study aims to determine and obtain a clear picture of supportive supervisor, empowerment, and organizational citizenship behavior; and to determine the impact of supportive supervisor and empowerment towards organizational citizenship behavior of employees in PT Setia Makmur Cemerlang. Research used explanatory survey method, while the sample was taken from employees of the company. Research instrument (questionnaires) was used as primary data collection to explain the causal relationship between supportive supervisor and empowerment on organizational citizenship behavior of employees in PT Setia Makmur Cemerlang. Analysis used simple linear regression and multiple linear regression method. Result of this study shows that there is significant influence between supportive supervisor and empowerment towards organizational citizenship behavior.